1979
DOI: 10.1103/physrevlett.43.274
|View full text |Cite
|
Sign up to set email alerts
|

Lower-Hybrid-Wave Heating in the Alcator-ATokamak

Abstract: We report the results of injecting 90 kW of microwave power near the lower hybrid frequency into the Alcator-A tokamak through a two-waveguide array. The observed plasma heating is in disagreement with that expected from linear waveguide-plasma coupling theory. From these results and auxiliary rf probe measurements we infer the nonlinear formation of a high-&n wave power spectrum at the plasma edge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
46
0

Year Published

1980
1980
1995
1995

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 8 publications
4
46
0
Order By: Relevance
“…These results are in qualitative agreement with the observations of the Alcator A lower hybrid heating experiment, 7 which inferred a kz spectrum peaked. at i/b.…”
Section: Discussionsupporting
confidence: 91%
“…These results are in qualitative agreement with the observations of the Alcator A lower hybrid heating experiment, 7 which inferred a kz spectrum peaked. at i/b.…”
Section: Discussionsupporting
confidence: 91%
“…At these power levels significant deviations from linear coupling have been observed. The reflection coeflicient depends on the power density and becomes less sensitive to the phasing of adjacent waveguides [3,41. In other experiments one has observed a change in the power spectrunm, which is shifted to larger values of the longitudinal refractive index (n.), [5]. The purpose of this paper is to present a theory which will explain, at least qualitatively, these results.…”
mentioning
confidence: 75%
“…The model is electrostatic and the drift kinetic approximation is used for the electrons while full dynamics of ions are followed in time. 6 Figure 1 shows the time development of the potential, ecp k (t)/T e , (a) for a long wavelength, £^^ = 0.16, and (b) for a short wavelength, k ± p { = 1.2, and the frequency spectrum obtained from one of the one-dimensional simulations. Here, w i /m^ = 1837, T e /T { = l 9 tt e /u pe =5 (ratio of the electron gyrofrequency to the plasma frequency), k n /k ± = 0.1, v d /v the = lA, and L= 1024A are used where v d is initial electron-drift speed along the magnetic field, v the is electron thermal speed, and A is the computational mesh size.…”
Section: D% = -^G(^)(7-t)% (I)mentioning
confidence: 99%
“…Density fluctuation scattering becomes especially interesting in light of recent puzzling results of the Alcator-A lower-hybrid-heating experiment, where it was found that the power coupled to the plasma was independent of the phasing of the two wave-guide grills used to launch the microwaves, 6 thus indicating that the inaccessible part of the power spectrum was able to propagate to the plasma center and heat. Furthermore, a high level of density fluctuations, peaked at the limiter radius, 1 was observed in Alcator-A.…”
mentioning
confidence: 99%